Standarisasi produk dan strategi digital marketing untuk meningkatkan pemasaran pada UMKM VCO Bertuah - Sujarwati Sujarwati; Siti Fatonah; Bernadeta Leni Fibriarti; Silvera Devi Sy; Oswati Hasanah; Arini Arini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
VCO Bertuah is an MSME in Pekanbaru that produces virgin coconut oil. Bertuah VCO has legality permits in the form of IUMK, NIB and P-IRT Certificate. However, Bertuah VCO does not have a halal certificate, BPOM distribution permit, and product SNI. The marketing of Bertuah VCO products is mostly done online, especially through social media platforms such as Facebook and Instagram. Other digital marketing strategies such as youtube and websites have not been carried out. Based on the results of the activity, it can be concluded that UMKM need assistance to take care of business legality. It is necessary to have active communication between UMKM and government agencies in charge of business licensing. Assistance activities have succeeded in increasing partners' understanding of the business legality management procedures. Assistance activities are very helpful for partners in preparing documents for business legality requirements. Assistance activities increase partners' understanding of digital marketing strategies through the website, instagram and youtube. Assistance activities help partners prepare advertising content in the form of product photos, instagram feed designs, video testimonials, and good ad copywriting.